Metal-free synthesis of N-fused heterocyclic iodides via C–H functionalization mediated by tert-butylhydroperoxide. Issue 82 (1st September 2015) - Sharma, Krishna K.; Patel, Dhananjay I.; Jain, Rahul
Abstract : Direct, regioselective and metal-free synthesis of fused N-heterocyclic iodides is reported. Abstract : Direct, regioselective and metal-free synthesis of fused N-heterocyclic iodides is reported. This regioselective C–H functionalization is mediated by tert -butylhydroperoxide (TBHP), via dual activation of molecular iodine and a heterocyclic substrate, resulting in the in situ generation of electrophilic iodine species (I + ), and free radical(s) t BuO˙ or t BuOO˙, driving the iodination reaction.